Prognosen zur Ost-West-Wanderung nach der deutschen Wiedervereinigung - Sascha Wolff (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2007)
The fall of the Berlin Wall in November 1989 and the subsequent reunification process between the former centrally planned GDR and the market-oriented Federal Republic of Germany, rapidly raised fears about mass migration movements from the eastern to the western part. The anxiety of an inundation of the western German labour market with cheap labour from the east weighed heavily on the heads of many party and labour union officials. In this context many studies were developed that try to predict the east-west German migration volume. Thus it is the objective of this paper to give an overview over the current state of economic research on migration forecasts in the east-west German context. At this juncture the main studies within this area will be described and critically discussed particularly with regard to their ex post forecast quality. Principally two types of analyses can be distinguished. On the one hand there are migration forecasts which are based on autonomous simulation or explanatory models. However, there are only a small number of these studies. Moreover most of these were developed at the beginning of the 1990s and are thus not very up to date. On the other hand there are migration predictions or better migration assumptions in the east-west German context, which have been developed within the scope of population forecasts and are in many cases based on the method of trend extrapolation. Such a critical review of existing east-west German migration forecasts seems to be requisite and meaningful against the backdrop of solidified economic disparities between east and west Germany. It will also provide a foundation for the development of a new forecast based on amore updated explanatory model.
Keywords: J11; J61; J62; R23; 330; migration forecasts; east-west German migration; Binnenwanderung; Regionale Arbeitsmobilität; Prognose; Neue Bundesländer; Alte Bundesländer; Prognoseverfahren; Kritik; Deutschland